The Influence of Financial Behavior and Operational Efficiency on Financial Performance with Financial Performance as a Moderating Variable at PERUMDA Air Minum Lae Nchiho Dairi - Isbet Yani; M. Irsan Nasution; Renny Maisyarah (International Journal of Economics and Management Sciences, 2025)
The Regional Drinking Water Company (Perusahaan Daerah Air Minum/PDAM) Lae Nciho, Dairi Regency, faces significant challenges related to the low level of financial literacy and financial behavior of its human resources, which negatively affect financial performance, particularly the Return on Equity (ROE) indicator. A lack of understanding and discipline in internal financial management has led to waste and operational inefficiency. This phenomenon highlights the importance of improving financial literacy and financial behavior as a strategic effort to enhance the company’s efficiency and profitability. The purpose of this study is to examine and analyze the influence of human resources’ financial behavior and operational efficiency on financial performance, with financial literacy serving as a moderating variable. This research applies a quantitative descriptive approach, using data analysis with the SEM PLS 3.0 method. The study involved a total population and sample of 70 employees of the Regional Drinking Water Company (Perumda Air Minum) Lae Nciho in Dairi Regency, particularly those working in finance and operations divisions, selected through purposive sampling techniques. The findings reveal that, partially, the variables of human resources’ financial behavior and operational efficiency significantly influence financial performance and affect financial literacy. Moreover, financial literacy significantly influences financial performance. However, simultaneously, financial behavior and operational efficiency do not significantly affect financial performance when moderated by financial literacy.